Memulai Proses Pembelajaran Bola Basket Dengan Bentuk-Bentuk Permaianan Rakyat Yang Kreatif dan Relevan Bagi Anak Usia SD/MI - Kusmiyati Kusmiyati (Yinyang: Jurnal Studi Islam Gender dan Anak, 2019)
The purpose of this article is to design a basketball learning process for elementary school / MI children to achieve goals. That the basketball learning process has a very broad goal Basketball learning not only teaches how students should master the basic techniques of the game correctly. Another more important goal is to develop the character of students to be more responsible, disciplined, tollerant, cooperate, makes decision correctly and quickly. The design of basketball learning should be packaged in a more interesting way. Interesting learning is filled with something unique. One thing that can be done by the teacher is by starting to provide a series of simple games that are interesting and relevant to basketball games. The form of the game leads to throwing activities (baiting / Passing) and catching that is much needed in basketball games.